Terahertz Angle‐Multiplexed Metasurface for Multi‐Dimensional Multiplexing of Spatial and Frequency Domains. Issue 10 (6th September 2020) - Wang, Ling; Yang, Yang; Deng, Li; Hong, Weijun; Zhang, Chen; Li, Shufang
Abstract: Increasing information capacity is crucial for high‐capacity and high‐speed communication, especially for sub‐terahertz communication. Over the last decade, spatial multiplexing based on the orbital angular momentum (OAM) by adopting a multi‐mode OAM metasurface has attracted a lot of attention. However, current metasurface‐based OAM multiplexing methods suffer from complex and limited multiplexing channels. In this paper, a novel method to realize multi‐dimensional multiplexing combining OAM and frequency based on an angle‐multiplexed metasurface over a broadband terahertz region is proposed and investigated. A frequency‐independent phase profile formula of the angle‐multiplexed metasurface is derived. A reflective metasurface operating from 0.25 to 0.35 terahertz (THz) is designed based on this formula. For proof of concept, nine‐channel multiplexing is illustrated based on this novel method. The simulation results verify that nine‐channel off‐axis left‐hand circularly polarized beams are converted to nine orthogonal coaxial beams. Besides, according to the conventional method for OAM multiplexing, an angle‐multiplexed reflective metasurface working at 0.3 THz is designed for comparison. The simulation results show that only three‐channel multiplexing can be obtained by this model with nine‐channel incident waves. The proposed method has a great potential to enhance the transmission capacity of the communication system. Abstract : A novel method to realize multi‐dimensional multiplexing combining OAM and frequency based on an angle‐multiplexed metasurface over a broadband terahertz region is proposed and investigated. A frequency‐independent phase profile formula of the angle‐multiplexed metasurface is derived. A reflective metasurface operating from 0.25 to 0.35 THz is designed. Nine‐channel multiplexing is illustrated based on this novel method.